Leaves of Absence and Presenteeism Among Canadian Teachers: Mental Health Challenges, Frequency, Impact, Facilitators, and Barriers - Ferguson, Kristen; Tulk, Christine; Corrente, Melissa; Rodger, Susan; Bourgeault, Ivy Lynn (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2026)
Using survey data from 733 teachers, we explored leaves of absence and presenteeism due to mental health challenges among Canadian teachers. Almost 40% of teachers had taken a formal leave of absence due to mental health concerns, with no significant difference by gender or grade-level taught. Having a supportive partner/family was the most cited facilitator of taking a leave, followed by having financial coverage. The most cited barrier to taking a leave was the impact it would have on students, followed by an unsupportive supervisor. The majority of teachers in our study experienced sickness presenteeism due to mental health challenges.